Gastrointestinal Microbiome Dysbiosis in Infant Mice Alters Peripheral CD8+ T Cell Receptor Signaling - Gonzalez-Perez, Gabriela; Lamousé-Smith, Esi S. N. (Frontiers in Immunology, 2017)
We recently reported that maternal antibiotic treatment of mice (MAT) in the last days of pregnancy and during lactation dramatically alters the density and composition of the gastrointestinal microbiota of their infants. MAT infants also exhibited enhanced susceptibility to a systemic viral infection and altered adaptive immune cell activation phenotype and function. CD8+ effector T cells from MAT infants consistently demonstrate an inability to sustain interferon gamma production in vivo following vaccinia virus infection and in vitro upon T cell receptor stimulation. We hypothesize that T cells developing in infant mice with gastrointestinal microbiota dysbiosis and insufficient toll-like receptor exposure alters immune responsiveness associated with intrinsic T cell defects in the T cell receptor signaling pathway and compromised T cell effector function. To evaluate this, splenic T cells from day of life fifteen MAT infant mice were stimulated in vitro with anti-CD3 and anti-CD28 antibodies prior to examining the expression of ZAP-70, pZAP-70, pErk1/2, c-Rel, total protein tyrosine phosphorylation and IFN-gamma (IFN-γ) production. We determine that MAT infant CD8+ T cells fail to sustain total protein tyrosine phosphorylation and Erk1/2 activation. LPS treatment in vitro and in vivo, partially restored IFN-γ production in MAT effector CD8+ T cells and reduced mortality typically observed in MAT mice following systemic viral infection. Our results demonstrate a surprising dependence on the gastrointestinal microbiome and TLR ligand stimulation toward shaping optimal CD8+ T cell function during infancy.